The effect of harvest time on the quantity and chemical composition of jasmine (Jasminum multiflorum L.) essential oil - Ahmad, S.H.; Malek, A.A.; Gan, H.C.; Abdullah, T.L.; Rahman, A.A. (International Society for Horticultural Science, 1998)
The quantity and chemical composition of essential oil from flowers of jasmine (Jasminum multiflorum L.) harvested in the morning (8.00 a.m.) and evening (6.00 p.m.) were compared. Flowers from each harvest time were extracted for their essential oil by the Soxhlet extraction method. Chemical composition of the essential oil was analysed by GC/MS. Harvest time did not affect the quantity of jasmine concrete extracted from the jasmine flowers. However, harvest time significantly affected the chemical composition of the jasmine concrete. The concentrations of indole and cis-jasmone compounds that characterised jasmine oil, were higher in the jasmine concrete obtained from morning-harvested flowers compared to the evening-harvested flowers. As such the quality of jasmine concrete obtained from morning-harvested flowers was better than jasmine concrete obtained from evening-harvested flowers. Jasmine concrete extracted from flowers harvested in the morning also contained higher concentrations of the following aroma-bearing compounds, benzyl alcohol, linalool and benzyl acetate, compared to concrete from evening-harvested flowers. Aroma-bearing compounds such as eugenol, benzyl benzoate, farnesol, methyl palmitate and methyl salicylate showed higher concentrations in the jasmine concrete obtained from evening-harvested flowers. Morning harvesting of jasmine for oil extraction is recommended.